Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae)Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae) - Peris-Felipo, Francisco Javier; Belokobylskij, Sergey A. (Zootaxa, 2018)
The first comprehensive revision of the Nearctic and Neotropical species of the genus Dinotrema Foerster, 1863 is provided. Twenty-two species of this genus are redescribed and illustrated. The following new combinations are suggested: D. floridensis (Shenefelt, 1974), comb. nov.; D. ephemera (Viereck, 1917), comb. nov.; D. foliformis (Fischer, 1969), comb. nov.; D. latitergum (Fischer, 1969), comb. nov.; D. lobidens (Fischer 1969), comb. nov. and D. longibasis (Fischer 1969), comb. nov. Dinotrema bucculatricis (Fischer 1969) is synonymized with D. angusticorne (Fischer 1969), syn. nov. Dinotrema sublatitergum (nom. nov.) is new name for junior homonym Dinotrema latitergum (Fischer, 1975), not D. latitergum (Fischer, 1969). The key to all New World species of Dinotrema is compiled for the first time.